Night Job - Hesse, Karen; Karas, G. Brian (Somerville, Massachusetts : Candlewick Press, 2018)
What's it like to work at night, while the rest of the city is asleep? This story of a boy and his father is a tribute to an enduring, everyday sort of love.
Keywords: Children of working parents -- Juvenile fiction; Work and family -- Juvenile fiction; Fathers -- Juvenile fiction; Fathers and sons -- Juvenile fiction; Night work -- Juvenile fiction; School custodians -- Juvenile fiction; Children of working parents -- Fiction; Work and family -- Fiction; Fathers -- Fiction; Fathers and sons -- Fiction; Night work -- Fiction; School custodians -- Fiction